Sulfur-related metastable luminescence center in silicon - Mason, P.W.; Sun, H.J.; Ittermann, B.; Ostapenko, S.S.; Watkins, G.D.; Jeyanathan, L.; Singh, M.; Davies, G.; Lightowlers, E.C. (My University, 1998)
Optical detection of magnetic resonance (ODMR) and photoluminescence (PL) studies are described for the sulfur-related metastable defect in silicon first reported by Brown and Hall. It is established that its two configurations, A and B, are of triclinic (C1) symmetry, and the incorporation of a single impurity atom with nuclear spin I=3/2 is confirmed directly by resolving its hyperfine structure in each ODMR spectrum. Detailed study of the conversion kinetics indicates the dominant A →B mechanism under below band-gap excitation to be the result of direct optical excitation, not the result of exciton capture or the energy release accompanying the luminescence. The barrier for thermally activated B→A return is 0.10±0.01 eV, with no evidence of an intermediate configuration. Stress-induced splittings of the PL are satisfactorily analyzed as the sum of that for a highly localized hole plus that for a shallow Coulombically bound effective-mass electron. A tentative model is proposed involving a substitutional sulfur atom paired with an interstitial copper atom in two different nearby configurations. The low symmetry results from the tendency of the Cu interstitial to go off-center from the tetrahedral interstitial position.